The Application of Hermeneutics in Indonesia as a Koranic interpretation Method - Imarotuz Zulfa (Kuras Institute, 2024)
An examination of the interpretation of the Koran that elicits contentious topics in the contemporary post-modern era is a fascinating subject to explore. Hermeneutics, which originated in Ancient Greece, has been included in the process of understanding the Koran, as discussed in this article. A discussion ensued concerning the advent of the hermeneutical approach when employed in the interpretation of the Koran. Is it possible to employ a hermeneutical methodology for the interpretation of the Koran? Hermeneutics provides a solution to contemporary interpretive disputes by offering a systematic and comprehensive approach to understanding and interpreting texts. In this inquiry, the author analyzes multiple perspectives on hermeneutics held by interpretive figures in Indonesia. This article highlights the importance of science as a catalyst for change in the contemporary era, emphasizing that it should not be disregarded or dismissed. In its pursuit of scientific advancement, it consistently adapts to contemporary knowledge and practices. However, it also remains grounded in ancient traditions, specifically by referring back to the Quran and Hadith.